2022
DOI: 10.3390/pathogens12010033
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIF-1α and Genes Involved in Glucose Metabolism Is Increased in Cervical Cancer and HPV-16-Positive Cell Lines

Abstract: Cervical cancer (CC) is the most common cancer in women in the lower genital tract. The main risk factor for developing CC is persistent infection with HPV 16. The E6 and E7 oncoproteins of HPV 16 have been related to metabolic reprogramming in cancer through the regulation of the expression and stability of HIF-1α and consequently of the expression of its target genes, such as HIF1A (HIF-1α), SLC2A1 (GLUT1), LDHA, CA9 (CAIX), SLC16A3 (MCT4), and BSG (Basigin or CD147), which are involved in glucose metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
(84 reference statements)
1
8
1
Order By: Relevance
“…S7). Also, previous work showed that in normal cervical cells, LDH-A expression levels were significantly lower than in cervical cancer cells [13, 49]. However, in normal cells (NKE and HaCaT), we find that the dose of DCF chosen for this study (175 µM, IC 50 in HeLa cells) causes only 10% cell death compared to cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…S7). Also, previous work showed that in normal cervical cells, LDH-A expression levels were significantly lower than in cervical cancer cells [13, 49]. However, in normal cells (NKE and HaCaT), we find that the dose of DCF chosen for this study (175 µM, IC 50 in HeLa cells) causes only 10% cell death compared to cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…These results were compatible with the results of the researcher, as they indicated the presence of the close association of HIF-1α with TLR4 in cervical cancer caused by HPV infection, and detected changes in the RNA content of HIF-1α in each group to explore their correlation. The RNA content of HIF-1α was similar to TLR4, and a suggestion from these results was that the expression HIF-1α was positively associated with the expression of TLR4 in the cervix (24).…”
Section: Discussionmentioning
confidence: 61%
“…An additional effect of the presence and accumulation of HIF-1a in tumors is presumed to be the contribution to tumor chemoresistance by obstructing drug transport and uptake, whereas its overexpression is linked to worse prognosis for patients with cervical cancer [ 39 , 42 ]. On the other hand, a molecule that has given signs of decreasing cancer cell resistance to chemotherapeutics in addition to inhibiting several of the hallmarks of cancer, like proliferation, tumor invasion and metastasis, is microRNA-143 [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%